VIEWING THE ISLAMIC FINANCIAL SYSTEM, ISLAMIC VIEWS AND ANSWERS ABOUT CRYPTOCURRENCY - Binta Tsulutsi Mukhoyyaroh (Khazanah: Jurnal Mahasiswa, 2022)
Cryptocurrency is a digital or virtual currency that created due to technological advances. Its purchase transactions take advantage of technological developments that can be done online without going through a bank intermediary, enhanced with the advantages of Blockchain technology. However, cryptocurrency investments have a high risk on their profit and loss value. It isn’t enough to get there, cryptocurrencies also still don’t get the legality in Indonesia. This discussion aims to get clarity on cryptocurrency investments and transactions, also get answers to cryptocurrency law according to Islamic sharia. Based on qualitative descriptions and review of literature studies. The result of this study is that the Islamic financial system provides a view on cryptocurrency investments and transactions with a clear and sourced law from the Qur’an, As-Sunnah, and the results of the cleric’ ijtihad. Based on Islamic sharia, investments and transactions used by cryptocurrencies contain elements of maysir (betting) and gharar (uncertainty) because they risk investment goods with unclear value of assets and their real form. The conclusion of this study is that users of cryptocurrencies are justified haram lighairihi as well as syubhat for those who still have doubts. Keywords : Cryptocurrency, Islamic sharia